2021
DOI: 10.1055/a-1382-2898
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral and Virucidal Properties of Essential Oils and Isolated Compounds – A Scientific Approach

Abstract: Essential oils and isolated essential oil compounds are known to exert various pharmacological effects, such as antibacterial, antifungal, antiviral, anti-inflammatory, anti-immunomodulatory, antioxidant, and wound healing effects. Based on selected articles, this review deals with the potential antiviral and virucidal activities of essential oils and essential oil compounds together with their mechanism of action as well as in silico studies involving viral and host cell-specific target molecules that are ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 131 publications
0
40
0
4
Order By: Relevance
“…Several EOs and their isolated components have been described in In Vitro and in vivo models as effective antiviral agents against DNA and RNA viruses in different host cell lines by obstructing different steps of the viral life cycle [ 38 ]. These impacts are mainly based on the oil composition of mono- and sesquiterpene hydrocarbons together with phenolic, alcoholic, and other oxygenated other components [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several EOs and their isolated components have been described in In Vitro and in vivo models as effective antiviral agents against DNA and RNA viruses in different host cell lines by obstructing different steps of the viral life cycle [ 38 ]. These impacts are mainly based on the oil composition of mono- and sesquiterpene hydrocarbons together with phenolic, alcoholic, and other oxygenated other components [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several EOs and their isolated components have been described in In Vitro and in vivo models as effective antiviral agents against DNA and RNA viruses in different host cell lines by obstructing different steps of the viral life cycle [ 38 ]. These impacts are mainly based on the oil composition of mono- and sesquiterpene hydrocarbons together with phenolic, alcoholic, and other oxygenated other components [ 38 , 39 ]. Several EOs have been recognized for their antiviral activities against a diversity of viruses, including human immunodeficiency virus (HIV), human herpes virus (HSV), avian influenza A virus (H5N1), influenza A virus (H1N1) and Zika virus [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, numerous studies demonstrated the wide pharmacological spectrum of EOs, including: antimicrobial [7,8], antifungal [9], antiparasitic [10], antiviral [10,11], insecticidal [12], anticarcinogenic [13][14][15][16], immunomodulatory [17], anti-inflammatory and antioxidant [14]. Nevertheless, the chemical composition of obtained EOs can unfortunately be different depending on the chosen method, geographical origins, the season, the type of soil and the agricultural conditions in which plants have grown.…”
Section: Introductionmentioning
confidence: 99%